2014
DOI: 10.7314/apjcp.2014.15.6.2841
|View full text |Cite
|
Sign up to set email alerts
|

Family History Attributes and Risk Factors for Breast Cancer in Turkey

Abstract: Background: When dealing with breast cancer, early detection is closely associated with determining and closely monitoring high risk groups. The aim of this study was to determine the preventable risk factors that are specific for our country, and to understand which risk factors were most predominant. Materials and Methods: The study was planned as a case-control design. Women diagnosed with breast cancer who visited the Surgery, Obstetrics and Gynaecology, and Radiation Oncology outpatient clinics of the Izm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
(29 reference statements)
1
4
2
Order By: Relevance
“…Family history of breast cancer is another established risk factor (Deirdre et al, 2002). A similar study conducted in Turkey revealed that the risk increases 5.7 times in a woman who has a first degree relative suffering from breast cancer (Gokdemir-Yazar et al, 2014). In our study, a total of 15% women reported to have a positive family history for breast cancer which is slightly less than the percentage observed among Female British University Students which was reported to be 17.2 % (Kanayo et al, 2010).…”
Section: Discussioncontrasting
confidence: 55%
“…Family history of breast cancer is another established risk factor (Deirdre et al, 2002). A similar study conducted in Turkey revealed that the risk increases 5.7 times in a woman who has a first degree relative suffering from breast cancer (Gokdemir-Yazar et al, 2014). In our study, a total of 15% women reported to have a positive family history for breast cancer which is slightly less than the percentage observed among Female British University Students which was reported to be 17.2 % (Kanayo et al, 2010).…”
Section: Discussioncontrasting
confidence: 55%
“…It is well documented that family history of cancer increases the risk to certain types of cancer (Murff et al, 2004). For example, the presence of breast cancer among first degree relatives increased the risk of developing breast cancer 5.7 times and adults who had relatives with any types of cancer advised to adapt a healthy lifestyle to decrease the risk (Lotreane tal., 2013;Gokdemir-Yazar et al, 2014). Thus, the majority of women in western countries were able to identify that family history of breast cancer is a risk factor for breast cancer (Breslow et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…34 It has been determined that women have a greater risk of breast cancer if there is a family history of cancer. 35 In our study, 25.50% of the women had first-degree relatives cancer history, 14.20% had breast cancer in their family, and 14.60% lung cancer. Participants were also given information and resources of health literacy, not only about breast-cervix cancer but also about healthy-life styles.…”
Section: Suspected Malignity Biopsy Advised Further Investigation Needed Healtymentioning
confidence: 48%